Model Edutorisme : Pengelolaan Integrasi Pendidikan dan Rekreasi Meningkatkan Data Tarik di Kawasan Wisata Tugu Pahlawan Surabaya - Yoseph Agung Priyo Widodo; Damiasih Damiasih; Isdarmanto Isdarmanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This article describes an edutourism model that integrates management between tourism areas and education as a strategy to increase the attractiveness of potential tourists. The Tugu Pahlawan area of ​​Surabaya City needs to develop an edutourism concept with the aim of maintaining cultural heritage, namely remembering the history of the struggle, and also needs to be an educational medium for visitors. Both of these things must go hand in hand to increase public interest, especially cultural innovation and entertainment. The purpose of this study is to apply the concept of edutourism and management of the Tugu Pahlawan area so that it becomes an object of historical education and entertainment tourism. The concept used in this study is edutorism using strategies from the results of the SWOT analysis used to explore potential and formulate programs. The method used is quantitative with a descriptive approach by collecting primary and secondary data. The results of this study are the potential for why development needs to be carried out, namely physical and non-physical potential. Physical in the form of buildings, objects and monuments that can be seen while non-physical are the values ​​contained in the physical. In addition, non-physical also includes activities to attract potential tourists such as music, classical drama, bazaars and other education. The potential analyzed becomes a SWOT matrix which is used for the next formulation. SWOT produces development strategies in management management such as planning, implementation, supervision and evaluation monitoring.